The New Life Market. Issue 3 (20th June 2013) - Blake, David; Cairns, Andrew; Coughlan, Guy; Dowd, Kevin; MacMinn, Richard
ABSTRACT : The huge economic significance of longevity risk for corporations, governments, and individuals has begun to be recognized and quantified. By virtue of its size and prevalence, longevity risk is the most significant life‐related risk exposure in financial terms and poses a potential threat to the whole system of retirement income provision. This article reviews the birth and development of the Life Market, the new market related to the transfer of longevity and mortality risks. We note that the emergence of a traded market in longevity‐linked capital market instruments could act as a catalyst to help facilitate the development of annuity markets both in the developed and the developing world and protect the long‐term viability of retirement income provision globally.